Plan de negocios de la empresa Aguahass, para exportar aguacate hass de Colombia a Barcelona (2018)
This work is a business plan for the export of Hass avocado by the company AguaHass, to fulfill this purpose, the company will create a responsible agency for international trade activities, which will be pending exports of Hass avocado even wholesaler located in the city of Barcelona (Spain). A market study was conducted where it is observed that the city of Barcelona, is a viable destination to make exports of Hass Avocado, because in this place there is a great acceptance of this fruit, for this reason there are large volumes of import A technical and financial study was also carried out to assess what the AguaHass company needs to carry out its export plan to Barcelona and the amount of capital that must be invested to execute this project.